Physics Learning Assistance Based on Guided Discovery Learning Using PhET Simulations at SMAN 1 Kediri - Zainuri, Baiq Nabila Saufika; Ayub, Syahrial; Hasanah, Faridatun (Indonesian Journal of Education and Community Services, 2023)
This community service activity aims to assist students at SMAN 1 Kediri in understanding physics concepts through the Guided Discovery Learning (GDL) model assisted by PhET simulations. This activity involved one X grade science class as the main subject. The implementation method included the preparation stage, the implementation stage (guidance on the implementation of the GDL model), and the qualitative evaluation stage through observation and analysis of student work. The results of the assistance show the enthusiasm and active involvement of students in exploring physical phenomena digitally. Despite facing constraints in terms of equipment and internet connection, the use of a rotation system and the offline version of the PhET application actually strengthened collaboration and peer tutoring among students. Qualitative discussions based on Student Worksheets (LKPD) confirmed that students were able to construct an understanding of the relationship between mass, velocity, and momentum independently and logically. In conclusion, the integration of the GDL model and PhET simulations effectively bridges the understanding of abstract concepts and overcomes the limitations of physical laboratory facilities in partner schools.